South Platte water conservation project a municipal-agricultural partnership - Brouwer, Carl, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2012)
Municipal water demand for the Front Range of Colorado is expected to increase substantially over the coming years. As these demands continue to grow, the pressure to dry up agricultural water supplies in the South Platte River basin continues to be more acute. The Northern Colorado Water Conservancy District (Northern Water) along with fifteen municipal water providers is presently in the permitting process for the Northern Integrated Supply Project (NISP). This project will consist of two distinct but integrated pieces – the new 170,000 acre-ft Glade Reservoir located northwest of Fort Collins, Colorado, and the South Platte Water Conservation Project (SPWCP). The SPWCP involves a pump station on the South Platte River which pumps water during the non-irrigation season to the proposed 45,600 acre-ft Galeton Reservoir located northeast of Greeley Colorado. The SPWCP will then deliver water during the summer to two large irrigation companies – the Larimer and Weld Irrigation Company and the New Cache Ditch Company. A like quantity of water that those companies would have diverted under their senior water rights will be exchanged upstream to Glade Reservoir for municipal use. This paper will discuss the formulation of the SPWCP project as well as the partnership that has been formulated with the ditch companies. In addition to an overview of issues associated with NISP, specific issues associated with the exchange with the ditch companies will be presented. In particular, the benefits of the municipal-agricultural partnership will be explained.
Irrigated agriculture responds to water use challenges
Presented at Irrigated agriculture responds to water use challenges - strategies for success: USCID water management conference held on April 3-6, 2012 in Austin, Texas.